Corrosion and mechanical properties study of car steel sheet - Ahmad Basyir, Sadan (2010)
This study is to understanding the corrosion behavior of deformed automobile parts, the effect on the mechanical properties and also to examine the microstructure changes due to corrosion. The methodology for this study started with preparing the sample which is deformed and undeformed steel for the immersion testing experiment and finished with the microstructure observation using optical microscope. Result is where all the data collected are analyzed and discussed with detailed explanation. Lastly, it covers the conclusion for the study. The study is hopefully will help automobile manufacturer in producing a better product for the automobile industry.